Qualitative Research in the Time of a Disaster Like COVID-19 (Revista Lusófona de Educação, 2020)
The year 2020 will go down in history as the year when the whole world was challenged with one invisible enemy that changed everything in human society in the 21st Century. It is the worst modern pandemic that has shaken all aspects of human life. It is clear that no one in any field was well prepared, if prepared at all, for COVID-19. The newness of this pandemic has given room for several qualitative research opportunities to help understand and address the social implications. In this paper, we discuss the social trends of COVID-19, the role qualitative research should play during a disaster such as this pandemic, and how to conduct qualitative research about and during such a disaster. This paper also introduces the Crisis Recovery Stages model that can help researchers move effectively in the production mode despite the disaster. The paper also generates ideas for current issues that can be addressed through and about qualitative research.Keywords: qualitative research; COVID-19; crisis recovery stages model